2018
DOI: 10.1111/jop.12683
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of a century of research on oral erythroplakia and leukoplakia

Abstract: We identified the leading journals as well as the leading authors and countries contributing to the research on OEL. International collaborative studies in the field are to be encouraged to refine strategies of oral cancer prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Sweden contributed most cancer articles followed by Denmark. Luukkonen-Gronow, (1988) Another study was conducted by Foy et al, (2018) to provide a descriptive overview of the global research activity on Oral Erythroplakia and Leukoplakia over the past decades. A total of 5,098 published items (articles or reviews) were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Sweden contributed most cancer articles followed by Denmark. Luukkonen-Gronow, (1988) Another study was conducted by Foy et al, (2018) to provide a descriptive overview of the global research activity on Oral Erythroplakia and Leukoplakia over the past decades. A total of 5,098 published items (articles or reviews) were identified.…”
Section: Discussionmentioning
confidence: 99%
“…First, they adopted the following query for search strategy: leukoplakia (or leucoplakia), erythroplakia, and erythroleukoplakia (and corresponding terms with plural form, egg leukoplakias). 1 The authors seem to ignore the criteria where used for inclusion or exclusion. Indeed, they ignored the fact that the exclusion of oral hairy leukoplakia which associated with the HIV/AIDS is not a potentially malignant disorder.…”
Section: Dear Editormentioning
confidence: 99%
“…Pojam visoko citiranih članaka opisivan je u radovima različitih naučnih oblasti i imenovan na više načina, poput najcitiraniji radovi, klasici, vrhunski citirani radovi itd. Naučno-istraživački radovi, okarakterisani kao klasici ili vrhunski citirani radovi, bili su predmet istraživanja više disciplina, uključujući karcinom usne duplje [6,7,8], maksilofacijalnu hirurgiju [9,10], stomatološku implantologiju [3,11,12], endodonciju [13], ortodonciju [14,15], ili parodontologiju [16]. U većini sprovedenih bibliometrijskih studija analizirani su najcitiraniji članci preuzeti iz baze Web of Science Clarivate Analytics, koja je široko prepoznata kao najsveobuhvatniji izvor najuticajnijih časopisa širom sveta.…”
Section: Kratak Sadržajunclassified
“…Highly cited papers concept has been described in different fields and named as the most cited papers, classic publications, top cited articles etc. Research articles, classified as classic publications or top cited, were investigated in a variety of disciplines, including oral cancer [6,7,8], maxillofacial surgery [9,10], implant dentistry [3,11,12], endodontics [13], orthodontics [14,15], or periodontology [16,17]. Most of the conducted bibliometric studies analyzed the most cited articles retrieved from the Web of Science database by Clarivate Analytics, which has been widely recognized as the most comprehensive source of the highest impact journals worldwide.…”
Section: Introductionmentioning
confidence: 99%